(untitled) (Research, Society and Development, 2023)
Introduction: In March 2019, the World Health Organization (WHO) declared the COVID-19 infection to be pandemic. Since then, it is estimated that disorders such as depression and anxiety have increased by up to 25%. Recent WHO publications point out that 9.3% of the Brazilian population has been suffering from Anxiety Disorder (AD), and 5.8% suffer from Major Depression Disorders (MDD), with these rates Brazil reaches the milestone of second place with people with MDD, and first place with people with AD. Objective: To analyze the use of herbal medicines during a pandemic period due to the COVID-19 infection, helping to treat disorders: anxiety and depression. Methodology: This research is a systematic review of the literature, with a qualitative and descriptive approach using the PICo strategy, which was searched in the Virtual Health Library, using 29 articles for this review. Results and Discussion: Both during the first critical moments of the pandemic, such as the first wave, and with its cessation, came the mental health pandemic, evidenced according to data from the World Health Organization (WHO) that during the first year of the pandemic, there was a 25% increase in the global prevalence of people with GAD and depression, where depression alone managed to reach about 44% of the population. Final Considerations: From these considerations, it can be seen that this research has shown an increase in the number of disorders during the pandemic, where people resort to non-drug treatments and that the population has become even more up-to-date on the use of herbal medicines.